(untitled) (Asian Journal of Medical and Biological Research, 2020)
In order to know the existing situation of different chemicals and aqua-drugs used for fish health management an investigation was conducted following a time frame of May, 2019 to October, 2019 at Rangpur district of Bangladesh. Data were collected from the randomly selected fish farmers, company representatives and chemical sellers through questionnaire interview, personal contact and Focus Group Discussion (FGD). Farmers were facing several water quality problems associated with different fish diseases. To overcome those obstacles they use variety of chemicals inclulding lime, salt, potassium permanganate, urea, TSP, phitkiri and copper sulphate. Farmers used different chemicals for various purposes like Aquapure, Biopond, Zeofresh, JV-zeolite, Zeorich, Megazeo plus, Geo-ren etc. for pond preparation and water quality management; Sumithion, Engreb, I-mec, Sanmarine etc. for eradication of unwanted species; Oxymax, Oxymore, Oxylife, Aci-ox, Oxyrich, Oxy-aqua, Oxyren etc. to increase oxygen concentration and Gasonil, Gastrap, Bioaqua-50, Gasonex, Metrix, Pondkleen etc. for reducing harmful gases in pond water. Used disinfectants like Timsen, Virex, Polgard+, , Micronil etc.; antibiotics include Renamycin, Eskamycin, Bactitab, Cotrim vet bolus, Chemycin, Aquamycin etc.; Aqua photo, Safegut, Biomax, Profs, Pond care etc. were the used probiotics where various growth promoters include Panvit aqua, Nutrigel, Aquazyme, Spa gelly, Charger gel etc. Some problems were reported regarding the use of chemicals such as their indiscriminate use, method of application, time of application and inappropriate doses. Asian J. Med. Biol. Res. June 2020, 6(2): 283-293